Comparative analysis of vaginal misoprostol 400 and 600 single dose for second-trimester termination of pregnancy-a prospective randomized trial - R., Rashmi V.; Jain, Apoorva; Y., Neha G.; S., Sunil Kumar K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: This study was done to compare two dosing schedules of tablet misoprostol single dose 600 µg (M600) versus multiple doses 400 µg (M400), kept per vaginally for second termination of pregnancy and to analyze induction to abortion time, side effects, and failure to achieve termination of pregnancy. Methods: Women admitted for second-trimester pregnancy termination were considered. Inclusion and exclusion criteria were followed. The women were randomized into two groups, with one group receiving single dose of M600 per vaginal and the other one multiple doses of M400, and the two groups were compared in their outcomes. Results: In the present study no statistical significance was found between the two dosing regimens with regard to induction abortion interval, post-expulsion need for suction, and evacuation. Conclusions: The study revealed that the dose between M400 and M600 has not shown significance compared with two dosing regimens. Single dose M600 can be considered for second-trimester pregnancy termination due to better compliance.